Squamous cell carcinoma of the small intestine: a case report and review of literature - Wang, Dandan; Li, Zhe-Xuan; Hu, Lanlin; Wang, Ying; Xu, Senlin; Xu, Chuan (Frontiers in Oncology, 2025)
Malignant tumors derived from the small intestine are rare, and most are adenocarcinomas. Primary squamous cell carcinoma of the small intestine is sporadic with a few cases reported in the literature. This study reports a case of a 56-year-old female who had a history of leakage of exudate for more than 40 years after an appendectomy. The patient presented with increasing leakage of exudate, abdominal pain, and fever this time, and was diagnosed with primary squamous cell carcinoma of the ileal after an intestinal resection and a fascial plasty. The patient declined to receive adjuvant chemotherapeutic treatment and died 9 months after the diagnosis of the tumor. Additionally, we reviewed 26 reported cases, summarized the clinical features and treatments, and discussed the potential pathogenesis and optional therapeutic strategies for primary squamous cell carcinoma of the small intestine.